Synthesis and Catalytic Properties of Palladium-N-Heterocyclic Carbene Complexes for cancer therapy: A comprehensive Review - Kumar, Avdhesh; Singh, Anju; Rajendiran, A.; Yadav, Aniket; Sachin, Sachin (Journal of Neonatal Surgery, 2025)
Heterocyclic compounds, characterized by cyclic structures containing heteroatoms such as nitrogen, oxygen, or sulphur, play a pivotal role in medicinal chemistry due to their diverse biological activities and applications in treating various diseases, including cancer. This research paper explores the synthesis and catalytic properties of novel palladium-N-heterocyclic carbene (NHC) complexes, specifically PEPPSI-type complexes, highlighting their effectiveness in facilitating direct arylation reactions of heterocycles. The study presents the synthesis of new imidazolinium salts and their conversion into stable palladium complexes with notable catalytic activity for arylation processes. Additionally, it examines the synthesis of spiro isoxazole-5-one derivatives and the development of iron-catalysed methodologies for generating pyrimidine and benzo carbazole derivatives, underlining the significance of iron catalysts in organic transformations. The research emphasizes the importance of optimizing reaction conditions and utilising earth-abundant catalysts to enhance the sustainability of chemical processes while achieving high yields and selectivity. Through mechanistic insights and experimental findings, this work contributes to the ongoing advancement of synthetic methodologies for producing heterocyclic compounds, which are essential in developing new therapeutic agents.